Pour une approche systémique du développement durable - Christine Voiron-Canicio (Développement Durable et Territoires)
First this paper presents some weakness and dysfunction in taking action for urban sustainability and gives the reasons. The fact that urban sustainability researchs do not take into account the systemic links between urban spaces and surrounding spaces, is one of the most important reasons. In the second stage the urban sustainability is analysed with an operational point of view. We present modelling methods which allow to understand how sustainable urban systems work and how to plan the city of the future according to sustainability.